KAJIAN POTENSI PRODUKSI PADI SERTA EVALUASI KINERJA OPERASI DAN PEMELIHARAAN SISTEM IRIGASI TANJUNG KERIAHAN DI KECAMATAN SIRAPIT KABUPATEN LANGKAT (The Study of Rice Potential Production with The Operational Work Evaluation and Maintenance of Tanjung Ker - Dian Permata Sari; Sumono Sumono; Nazif Ichwan (Universitas Sumatera Utara, 2017)
ABSTRACK Tanjung Keriahan as rice production area in Langkat Regency which served by technical irrigation system with target of rice productivity can reach its production potential.Achievement of the target was evaluated based on production target and performance of operation and maintenance of irrigation system in the period of 2011-2015. Some of the research indicators were potential production, productivity, production target, and rice landscaping indices and performance of operation and maintenance of irrigation system. The results showed that the average of potential production was 94,81 kw/ha, the average of productivity was 63,857 kw/ha, the average of production target was 66,908%, rice landscaping indices were 3 and performance of operation and maintenance of irrigation system was 3,61; classified in the very well category. Keywords: Irrigation System, Rice, Performance Evaluation,Tanjung Keriahan. ABSTRAK Tanjung Keriahan merupakan daerah penghasil beras di kabupaten Langkat yang dilayani oleh sistem irigasi teknis dengan target produktivitas padi yang dihasilkan dapat mencapai potensi produksinya. Ketercapaian target tersebut dievaluasi berdasarkan aras pencapaian produksi padi serta kinerja operasi dan pemeliharaan sistem irigasinya pada periode 2011 – 2015. Beberapa indikator penelitiannya adalah potensi produksi, produktivitas, aras pencapaian produksi dan indeks pertanaman padi serta kinerja operasi dan pemeliharaan sistem irigasi. Hasil penelitian menunjukkan potensi produksi rata – rata adalah 94,81 kw/ha, produktivitas rata – rata 63,857 kw/ha, aras pencapaian produksi rata – rata 66,908%, indeks pertanaman padi 3 serta kinerja operasi dan pemeliharaan sistem irigasi mencapai score 3,61 tergolong dalam kategori sangat baik. Kata Kunci : Evaluasi Kinerja, Padi, Sistem Irigasi, Tanjung Keriahan.